Green synthesis of upconversion nanocrystals by adjusting local precursor supersaturation under aqueous conditions - Li, Su (2023)
We describe a green synthesis of upconversion nanocrystals (UCNs) by adjusting local precursor supersaturation under aqueous conditions at low temperature with size and phase control as well as high production yield. The synthesis allows the separation of nucleation and growth, leading to the formation of small UCNs with a uniform size. Ultra-small alpha -phase UCNs (similar to 6.3 nm) and bright beta -phase UCNs (similar to 25.5 nm) have been synthesized.